PENERAPAN MODEL PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) BERBASIS MASYARAKAT DI ERA NEW NORMAL - Selvie Serly Rumagit; Apriles Mandome; Estefina Makausi; Priska Mawuntu (LPPM UNIMA, 2022)
The Covid-19 pandemic requires people to live a clean and healthy lifestyle in order to not only avoid but also to break the chain of the spreading of this deadly virus. However, it cannot be denied that the lack of knowledge and supporting infrastructure in the society is one of the main factors for the lack of proper implementation of Clean and Healthy Living Behavior (PHBS). This activity aims to increase the knowledge and awareness of the society, especially those in disease-prone areas such as final disposal sites (TPA), on Clean and Healthy Living Behavior. The method used was counseling or seminar in forms of lectures and demonstrations as well as the provision of infrastructure to support PHBS both at work and in public places. This activity gives a positive impact on the target society where it can be seen that there is an increase in knowledge and patterns of Clean and Healthy Living Behavior in the society as well as high society satisfaction on the activities carried out.